Programas de extensão universitária como instrumentos de requalificação urbana e assistência técnica aos municípios de minas gerais: estudo de caso bairro Nove de Março - Barbacena-MG - Luis Otavio Campos Faustino Vieira (2010)
The increasing number of graduated students in Architecture and Urbanism in Brazil had caused an overflow of professionals in which only about 40% actually, is being working this field. On the other hand, the building construction industry is developing at a fast pace. Cities are growing fast and, along with them, a number of underprivileged peripheries are sprawling. An obvious conclusion is that architects are being excluded from this process other professionals have been doing their job. To add to that, the Brazilian Institute of Architects revealed that in 2005, around 82% of the administrative government branches in Brazil have no architects in their staff. In view of these facts, it was clear that some measures had to be taken in order to create new jobs for recent graduates in administrative bodies of a number of localities. This is the aim of the Public Architecture programme to foster sustainable development and to increase life quality in a number of human settlements, by undertaking urban, social and cultural projects, having architecture students working in tandem with public policies boards. One of the Public Architecture programme was developed in a squatter settlement named Nove de Março, a neighbourhood located in the periphery of Barbacena - Minas Gerais. This dissertation presents the study of urban renewal based on populations demands and developed during 2006, with closed supervision from the local administrative branch and the support of the Architecture Scholl teachers, which results can be evaluated in here.